Causes and consequences of the relation between area and age of the ocean floor. - Parsons, B (1982)
The distribution of area of the ocean floor with age, t, is approximately described by dA/dt=C0(1-(t/tm)), where C0 is the rate of crustal generation and tm the maximum age. A linear differential area versus age relation can be explained by a balance between generation and consumption where consumption is uniformly distributed with age. The present distribution of consumption with age was estimated from the isochron map used to derive the area-age relation and a recently published set of angular velocity vectors describing present plate motions. The trenches appear to be distributed randomly with respect to age provinces in the oceans. Changes in the rate of plate generation and the distribution of consumption with age result in shifts in the area-age distribution. In turn, these shifts produce changes in the plate driving forces which act to restore the rate of plate generation and distribution of consumption to their initial states. This coupling between driving forces and the area-age distribution provides a feedback mechanism limiting the extent of any changes. A measure of the magnitude of shifts in the area-age distribution is given by global changes in sea level. The area-age relation can be combined with simple expressions for depth and heat flow versus age to obtain an empirical hypsometric distribution, parameterized in terms of age, and exact expressions for the heat loss from the ocean floor.-Author